Metal framework as a novel approach for the fabrication of electric double layer capacitor device with high energy density using plasticized Poly(vinyl alcohol): Ammonium Thiocyanate based Polymer Electrolyte - Brza, Mohamad A.; Shujahadeen, Aziz; Anuar, Hazleen; Ali, Fathilah; Hamsan, M.H; Kadir, M.F.Z; Abdulwahid, Rebar T. (Elsevier B.V., 2020)
High performance electric double-layer capacitors (EDLCs) based on poly (vinyl alcohol) (PVA): ammonium thiocyanate (NH4SCN):Cu(II)-complex plasticized with glycerol (GLY) have been fabricated. The maximum DC ionic conductivity (σDC) of 2.25 × 10-3 S cm-1 is achieved at ambient temperature. The X-ray diffraction (XRD) patterns confirmed that the addition of both Cu(II)–complex and GLY enhanced the amorphous region within the samples. Through the Fourier transform infrared (FTIR) the interactions between the host polymer and other components of the prepared electrolyte are observed. The FESEM images reveal that the surface morphology of the samples showed a uniform smooth surface at high GLY concentration. This is in good agreement with the XRD and FTIR results. Transference numbers of ion (tion) and electron (tel) for the highest conducting composite polymer electrolyte (CPE) are recognized to be 0.971 and 0.029, respectively. The linear sweep voltammetry (LSV) revealed that the electrochemical stability window for the CPE is 2.15 V. These high values of tion and potential stability established the suitability of the synthesized systems for EDLC application. Cyclic voltammetry (CV) offered nearly rectangular shape with the lack of Faradaic peak. The specific capacitance and energy density of the EDLC are nearly constant within 1000 cycles at a current density of 0.5 mA/cm2 with average of 155.322 F/g and 17.473 Wh/Kg, respectively. The energy density of the EDLC in the current work is in the range of battery specific energy. The EDLC performance was found to be stable over 1000 cycles. The low value of equivalent series resistance reveals that the EDLC has good electrolyte-electrode contact. The EDLC exhibited the initial high power density of 4.960 × 103 W/Kg